A mixed methods feasibility study of a ketogenic diet as treatment for Parkinson’s disease - Worster, Kate; Colgan, Dana; Vita, Alexandra; McClure, Christine; Buttolph, Lita; Hodges, Romilly; Senders, Angela; Erlandsen, Andy; Elbarbry, Fawzy; Zwickey, Heather (Frontiers in Nutrition, 2025)
ObjectivePeople with Parkinson’s disease (PD) have been shown to benefit from a ketogenic diet (KD). However, evidence suggests the traditional KD’s high dairy consumption may exacerbate PD symptoms. This patient-initiated study assessed the feasibility and acceptability of a novel ketogenic diet limiting dairy products in patients with PD. Quality of life and functional movements were also evaluated.MethodsTwelve people with PD followed a modified, low dairy KD for 12 weeks. We provided support and nutritional education to assist with adherence. Subjects recorded daily food diaries, from which total macronutrients were calculated. Every 4 weeks blood (complete blood count (CBC), lipid panel, vitamin D, beta-hydroxybutyrate, electrolytes), urinalysis (calcium, creatinine), vitals, height, weight, quality of life [Parkinson’s Disease Questionnaire-39 (PDQ-39)] and functional movement assessments [Unified Parkinson’s Disease Rating Scale (UPDRS), Freezing of Gait, mini-Balance Evaluation Systems Test (mini-BEST), 360° Turn] were collected.ResultsAll subjects completed the study and 75% recorded at least three-quarters of their daily food diary entries. Average macronutrient levels (70% fat, 18% protein, 5% net carbohydrate) and beta-hydroxybutyrate levels (p < 0.005) confirmed nutritional ketosis was maintained. Clinical improvements were found in total UPDRS, UPDRS Part III, miniBEST, Freezing of Gait, and quality of life. All participants lost weight; 58% reported no change in constipation and 8% reported improvement.ConclusionThis exploratory study deemed the modified ketogenic diet feasible and acceptable. Findings suggest a low dairy KD may provide similar benefits to a traditional KD for those with PD, while reducing potential risks associated with consuming higher amounts of animal dairy products.